They Must Have Done Something! Socioeconomic Status and Citizens’ Support for the Victims of Violence - Zizumbo-Colunga, Daniel (Victims & offenders, 2021)
Why do some victims of criminal atrocities mobilize the public while others do not? I argue that victims’ socioeconomic background systematically biases citizens’ evaluations. I use experimental methods to assess this claim among a representative sample of citizens and elites interviewed during the Mexican war on drugs. I find citizens to be more likely to dismiss victims as responsible for their misfortune when they come from lower socioeconomic strata, and that this bias is concentrated among elite and high-socioeconomic-status citizens. These findings have important implications for our understanding of the psychology of victim-blaming and the origins of justice inequality.